A STUDY ON THE SECOND YEAR STUDENTS’ FOREIGN LANGUAGE ANXIETY OF SPEAKING ENGLISH OF SMAN 8 PEKANBARU - Ratu Maharani Kharty Kea; Erni Erni; Novitri Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The objective of this research is to find out the extent of the second year students’ foreign language anxiety of speaking English of SMAN 8 Pekanbaru. This is a descriptive research that has only one variable applied. In conducting this research, there were 45 samples selected, using convenience sampling technique. A set of questionnaire was used to collect the data adapted from FLCAS (Foreign Language Classroom Anxiety Scale) designed by Horwitz et al (1986). There are two kinds of data that were analyzed in this research: primary data which are the students’ questionnaires and secondary data deriving from speaking scores from the English teacher. The result of the students’ questionnaire responses shows a mean score of 2.91, indicating a medium level of anxiety, whereas the students’ speaking scores indicating a good level with a mean score of 83. The results show that there is a tendency that students’ speaking scores decreases as their anxiety level increases.Keywords: Foreign Language Anxiety, Speaking Scores